2017
DOI: 10.1186/s40409-017-0099-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of the hyperalgesic activity of myotoxic Lys49-phospholipase A2

Abstract: BackgroundBothropstoxin-I (BthTx-I) is a Lys49-phospholipase A2 (Lys49-PLA2) from the venom of Bothrops jararacussu, which despite of the lack of catalytic activity induces myotoxicity, inflammation and pain. The C-terminal region of the Lys49-PLA2s is important for these effects; however, the amino acid residues that determine hyperalgesia and edema are unknown. The aim of this study was to characterize the structural determinants for the Lys49-PLA2-induced nociception and inflammation.MethodsScanning alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Furthermore, the enzymatic activity of OS2 was dependent of the N-and C-terminal regions, and the Nterminal region had a major role in the central nervous system neurotoxicity. An alanine scan of the Lys49-PLA2 from Bothrops jararacussu (BThTx-I) demonstrated distinct regions involved in the hyperalgesia and edema (Zambelli et al, 2017a). In this study, the mutant Arg118Ala lost both nociceptive and edematogenic properties, Lys115Ala and Lys116Ala lost the nociceptive effects without interfering with the edema formation and Lys122Ala lost the nociceptive properties and had weak inflammatory effects (Figure 1E).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 56%
See 2 more Smart Citations
“…Furthermore, the enzymatic activity of OS2 was dependent of the N-and C-terminal regions, and the Nterminal region had a major role in the central nervous system neurotoxicity. An alanine scan of the Lys49-PLA2 from Bothrops jararacussu (BThTx-I) demonstrated distinct regions involved in the hyperalgesia and edema (Zambelli et al, 2017a). In this study, the mutant Arg118Ala lost both nociceptive and edematogenic properties, Lys115Ala and Lys116Ala lost the nociceptive effects without interfering with the edema formation and Lys122Ala lost the nociceptive properties and had weak inflammatory effects (Figure 1E).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 56%
“…β-Bungarotoxin (β-BTX) from Bungarus multicinctus (Class I, Basic) (Uniprot P00617), OS2 from Oxyuranus scutellatus (Class I, Basic) (Uniprot Q45Z47), Myotoxin II from Bothrops asper (Class II, Basic) (Uniprot P24605), APP-D49 from A. piscivorus (Class II, Basic) (Uniprot P51972), BpirPLA2-I from Bothrops pirajai (Class II, Acid) (Uniprot C9DPL5), Bothropstoxin-1 (BThTx-I) from Bothrops jararacussu (Class II, Basic) (Uniprot Q90249), and Crotoxin B from Crotalus durissus terrificus (Class II, Basic) (Uniprot P24027). Green: N-terminal region critical for enzymatic and neurotoxic properties, C-terminal region essential for enzymatic activity and central Histidine in the catalytic site (Rouault et al, 2006), Yellow: C-terminal region with myotoxic properties (Lomonte et al, 1994;Nunez et al, 2001), Dark green: C-terminal region with anti-platelet aggregation activity (Teixeira et al, 2011), Gray: Lysin residues involved in the nociceptive, and/or endematogenic properties (Zambelli et al, 2017a) and Cyan: modified residues in the Crotoxin B which lead to alterations in the enzymatic, toxic, and pharmacological properties (Soares et al, 2001). (B-E) Cartoon representation of the three-dimensional structure of (B) β-Bungarotoxin with the PLA2 domain in red and knutiz domain in green (PDB 1BUN), (C) MitTx1 and ASIC1a channel complex with PLA2 domain in red, knutiz domain in green and ASIC1a channel in blue (PDB 4NTY), (D) Crotoxin B (PDB 2QOG) and (E) BThrTx1 (PDB 3HZD).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning alanine mutagenesis has been shown to be a useful strategy to study the structural determinants of the activities of Lys-49 PLA 2 . In this sense, Chioato et al (2002) [ 138 ] have demonstrated, for the BthTx-I, that the Arg115Ala and Arg116Ala mutants do not display membrane-damaging activities, whereas the Lys122Ala mutant lacks myotoxic activity. In addition, His48Gln substitution, which eliminates any possible catalytic activity, does not interfere with the membrane damaging properties of the toxin.…”
Section: Nociceptive Effects Of Animal Venom Spla 2 mentioning
confidence: 99%
“…While slowly ascending the force on the hindpaws of the animal gives that animal the freedom to voluntarily withdraw the paw as soon as the pain becomes unbearable or the operator can intervene and unload the paw as soon as the animal shows signs of struggle. Hence, assessement of mechanical allodynia (Ke et al, 2013, Bu et al, 2014, Xia et al, 2014, Bao et al, 2014a and mechanical hyperalgesia (Al-Rejaie et al, 2015, Whiteside et al, 2004, Ferrari et al, 2017, Zambelli et al, 2017, Griggs et al, 2016 (Koltzenburg et al, 1999).…”
Section: Trabecular Number (Tbn)mentioning
confidence: 99%